Factors Related to the Differential Preference for Cardiopulmonary Resuscitation Between Patients With Terminal Cancer and That of Their Respective Family Caregivers. (February 2016) - Hwang, In Cheol; Keam, Bhumsuk; Kim, Young Ae; Yun, Young Ho
There is little information regarding concordance between preferences for end-of-life care of terminally ill patients with cancer and those of their family caregivers. A cross-sectional exploration of cardiopulmonary resuscitation (CPR) preference in 361 dyads was conducted. Patients or family caregivers who were willing to approve CPR were compared with dyads who did not support CPR. The patient's quality of life was more associated with family caregiver's willingness than patient's willingness. A patient was more likely to prefer CPR than their caregiver in dyads of females and emotionally stable patients. A family caregiver showed stronger support for CPR if the patient had controlled pain or stable health and the family caregiver had not been counseled for CPR. Communications should be focused on these individuals to improve the planning of end-of-life care.